INFLUENCER MARKETING STRATEGIES AND THEIR IMPACT ON GEN Z SKINCARE PURCHASING DECISIONS - Nabila Aliffia; Dzaqy Shifa (UPT Publikasi Ilmiah UNISBA, 2026)
This article aims to investigate the effectiveness of influencer marketing strategies in fostering brand trust, which subsequently impacts the purchase interest and buying behavior of Gen Z. Using a quantitative survey and case study approach, data were collected from 150 Semarang students aged 17–26 who were exposed to local skincare promotions by social media influencers. Analyzed using Partial Least Squares Structural Equation Modeling. The results confirmed strong convergent validity, with all indicators showing factor loadings above 0.70. Influencer marketing was found to have a significant positive effect on purchase interest and purchase decisions, supporting Hypotheses H1 and H2. Additionally, mediation analysis revealed that purchase interest significantly mediates the relationship between influencer marketing and purchase decisions, confirming Hypothesis H3. These results indicate that influencer marketing significantly enhances consumer interest by fostering emotional trust and intimacy, while also influencing purchase decisions through increased brand awareness. Moreover, purchase interest mediates and reinforces the positive impact of influencer marketing on buying behavior.